DINAMIKA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH DASAR - Hartati, Afiatun Sri (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2015)
Abstract: The research revealsÂ  the actualÂ  issue PAIÂ  learningÂ  in SDN Gonggang 1 with the various problems that arise and attempt a solution. To answer this problem formulated the problem of how the implementation of learning and problems of anything that appears and attempts to solve it? The study used a qualitative approach to the subject of research is the PAI teachers and principals. Data collected by documents, observations andÂ  interviews. EnterprisesÂ  improveÂ  the objectivity and credibility of the data andÂ  interviews conducted withÂ  triangulation repeats. Data were analyzed accordingÂ  suggestion Miles and Huberman which consists of dataÂ  reduction, data display, and verification or conclusion. The results showed: 1) In general, if based on the average value of classes for subjects PAI is good enough. 2) The problem that arises is the problem of classroom management, assessment, limited allocation of time, and the problem of interaction of teachers and pupils. To overcome the problems are: a) Teachers PAI need to establish a pattern of classroom management approach to socio-emotional climate, b) teachers need to use multiple assessment tools to assess studentsâ affective attitude that scale, questionnaires, interviews, observation and self refort.Â Ø£Ø´ÙØª ØªÙØ§ ÙÙØ§Ø´ÙØ§ ÙÙØªÙ Ø¹ÙÂ Â  Ù ÙÙØ¹ØªÙØ§ PAI Ø©ÙÙØ¹ÙÙØ§ Ø©ÙÙØ´ÙØ§ ÙØ¹ ÙØ´ÙÙ Ø«ØØ¨ÙØ§Â Ø¡ÙØ´ ÙØ£ ÙÙØ§Ø´ÙÙ ÙÙØ¹ØªÙØ§ Ø°ÙÙÙØª Ø©ÙÙÙÙ Ø©ÙÙØ´Ù ØªØ¹Ø¶Ù Ø©ÙÙØ´ÙØ§ ÙØ°Ù ÙÙØ¹ Ø©Ø¨Ø§Ø¬ÙÙ .ÙØ ÙØ¥ ÙØµÙØªÙØ§ Ø©ÙÙØ§ÙÙÂ .Ø³Ø±Ø§Ø¯ÙØ§ ÙØ±ÙØ¯ÙÙ ÙÙÙØ¹ÙØ§ PAI ÙÙ Ø«ØØ¨ÙØ§ Ø¹ÙØ¶ÙÙ ÙØ¹ÙÙÙØ§ Ø¬ÙÙÙØ§ Ø©Ø³Ø§Ø±Ø¯ÙØ§ ØªÙØ¯Ø®ØªØ³Ø§ ØØ§ÙÙÙ ØªÙÙØ§ÙÙ ÙØ¯Ø¨ÙÂ Ø©ÙÙØ§Ø¯ØµÙÙ Ø©ÙØ¹ÙØ¶ÙÙ ÙØ³Øª ÙÙØ¹ ØªØ§Ø³Ø³Ø¤ÙØ§ .ØªÙØ¨Ø§ÙÙØ§Ù ØªØ§Ø¸ØÙÙØ§Ù ÙØ¦Ø§Ø«ÙÙØ§ ÙÙØ® ÙÙ Ø§ÙØ¹Ø¬ Øª ØªÙØ§ ØªØ§ÙØ§ÙØ¨ÙØ§Â ÙØ°ÙØ§ ÙØ§ÙØ±Ø¨ÙÙÙ Ø²ÙÙØ§Ù ØØ§ØªÙØ§ Ø§ÙÙÙ ØªØ§ÙØ§ÙØ¨ÙØ§ ÙÙÙØª Øª Ø¯ÙÙ .Ø«ÙÙØ«ØªÙØ§ Ø±Ø§Ø±ÙØª Ø¹Ù ØªÙØ±Ø¬Ø£ ØªÙØ§ ØªÙØ¨Ø§ÙÙØ§Ù ØªØ§ÙØ§ÙØ¨ÙØ§Â Ø§Ø°Ø¥ ØÙØ§Ø¹ ÙÙØ´Ø¨ )1 :Ø¬Ø¦Ø§ØªÙÙØ§ ØªØ±ÙØ¸Ø£ .Ø¬Ø§ØªÙØªØ³ÙØ§ ÙØ£ ÙÙØØªÙØ§Ù ØØªØ§ÙØ§ÙØ¨ÙØ§ Ø¶Ø±Ø¹Ù ØØªØ§ÙØ§ÙØ¨ÙØ§ ÙØ§Ø²ØªØ®Ø§ ÙÙ ÙÙÙØªÙÂ Ø£Ø´ÙØª ØªÙØ§ Ø©ÙÙØ´ÙØ§ ÙØ¥ )2 .Ø©ÙØ§ÙÙÙØ§ ÙÙÙ Ø§Ø¨ Ø¯ÙØ¬ ÙÙ PAI Ø©ÙØ³Ø§Ø±Ø¯ÙØ§ Ø¯Ø§ÙÙÙÙ ØªØ§ÙØ¨Ø·ÙØ§ Ø©ÙÙÙ Ø·Ø³ÙØªÙ Ø³Ø§Ø³Ø£ ÙÙØ¹Â .Ø°ÙÙÙØªÙØ§Ù ÙÙÙØ¹ÙØ§ ÙØ¨ ÙØ¹Ø§ÙØªÙØ§ Ø©ÙÙØ´ÙÙ ØÙÙØ²ÙØ§ ÙÙ Ø©Ø¯ÙØ¯Ù ØµÙØµØªÙ ØÙÙÙÙØªÙ ØÙØµÙØ§ Ø©Ø±Ø§Ø¯Ø¥ Ø©ÙÙØ´Ù ÙÙÂ ÙØ¹Ø§ÙØªØ¬ÙØ§ Ø®Ø§ÙÙÙÙ Ø©ÙÙØµÙØ§ Ø©Ø±Ø§Ø¯ÙØ§ Ø¬ÙÙ ÙÙ Ø·Ù Ø³ÙØ³Ø£Øª ÙØ¥ Ø©Ø¬Ø§Ø¨ PAI ÙÙÙØ¹ÙØ§ )Ø£ :ÙÙ ÙÙØ§Ø´ÙØ§ ÙÙØ¹ Ø¨ÙØºØªÙÙÂ Ø§Ø°ÙØ¨ ÙÙØ·Ø§Ø¹ÙØ§ Ø¨ÙØ·ÙØ§ ÙÙÙÙØ§ ÙÙÙÙØªÙ Ø©Ø¯Ø¯Ø¹ØªÙ ÙÙÙÙØª ØªØ§ÙØ¯Ø£ ÙØ§Ø¯Ø®ØªØ³Ø§ ÙØ¥ Ø©Ø¬Ø§Ø Ù Ø©ÙÙØ¹ÙÙ Ø§ÙÙØ¹Ù )Ø¨ ØÙÙØ·Ø§Ø¹ÙØ§Ù.ÙØµÙØ§ Ø±ÙØ±ÙØªÙ Ø©Ø¸ØÙÙØ§Ù ØªÙØ¨Ø§ÙÙØ§Ù ØªØ§ÙØ§ÙØ¨ØªØ³ÙØ§Ù ØÙØ¬ÙØ§Kata Kunci: PAI, pembelajaran, problematika